KETELADANAN KYAI DALAM MENCIPTAKAN BUDAYA RELIGIUS PADA PONDOK PESANTREN ANAK-ANAK - Subekti, Yusuf Agung; Mutamakin, Mutamakin (STAI Ma'had Aly Al-Hikam Malang, 2022)
Kyai is a charismatic leader for their santris (student in islamic boarding school) has existed in Indonesia since long time ago. The Pesantren (Islamic boarding school) was well known as Islamic educational institution to bring up children to read, write and living according to the guidance of the Koran. The core element of Pesantren are Kyai and his wife, students supervisors, teachers council, students, mosque, and curriculum, while teaching the Koran has become a sub-culture of its own. Establishing character education in very early age is urgent to form a positive sub-culture of personal life to face the challenge of modernization and globalization. Furthermore, many stakeholders stated that Pesantren is one of the educational institutions that can serve as a role model for character education in Indonesia. Two questions will be addressed in this paper is how Kyai’s role model can shape children's religious attitude of kids boarding school. This study focuses specifically on Pesantren Nur Mamba'ul Hisan Satreyan Kanigoro Blitar